Urban oasis a man-made beach resort in the city - Morales, Carem Ruth R.; De Leon, Ruby Teresa M. (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
Beaches are one of the best places to visit for relaxation and leisure. People often visit beaches in order to take some time off from stress and noise experienced in the city, especially in the workplace. Philippines, being an archipelago, has a lot of pristine beaches that are recognized globally. However, people nowadays are too focused on making a living that travelling for leisure is something they do not prioritize. In this fast-paced lifestyle we are now living, an out-of-town vacation is a luxury that most of us cannot afford ; most frequented beaches such as Boracay, Palawan, Cebu, etc. are often a plane ride away from the metro. As a solution to this, a man-made beach resort shall be constructed within the urban area attracting both local and international tourists. Replicating a natural beach resort environment, it shall house a man-made beach, leisure pools, wave pools, sleeping quarters, gym, spa, and many more. Urban Oasis aims to provide the people a relaxing beach vacation without breaking away from urban conveniences, satisfying the craving for the best of both worlds.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Seaside resorts -- Designs and plans